THE FOUNDATION OF PANCASILA IN THE FORMATION OF LEGISLATION USING THE OMNIBUS LAW METHOD - Sahnan Sahuri Siregar (Universitas 17 Agustus 1945 Semarang, 2023)
This article will try to provide an analysis of the role of Pancasila in the formation of legislation using the omnibus law method. The Omnibus Law is a new method in Indonesia and has experienced various polemics in society. The research results show that Pancasila is the source of all sources of law in Indonesia. This fact has emphasized that the formation of laws and regulations in Indonesia must not conflict with the values contained in Pancasila. In addition, Pancasila is a guiding principle in national legal politics so that no regulation can contradict the values of divinity and civilization, and no regulation can contradict human values. No regulation can be born that has the potential to damage the integrity of the ideology and territory of the nation and state of Indonesia. There should be no regulations that violate the principle of popular sovereignty, and the most important thing is that these regulations do not violate the principle of popular sovereignty. The most important thing is that these regulations do not violate the values of social justice.